Art 2125 Analysis of Determinants of Potential for Sharia Insurance Development in Singkuang Village, Mandailing Natal Sumatera Utara - Rian Dandi Pratama; Muhammad Syukri Albani Nasution; Imsar (Al Mashaadir : Jurnal Ilmu Syariah, 2026)
This study aims to quantitatively analyze the household economic protection needs and their relationship with the development of Islamic insurance in Singkuang Village, Muara Batang Gadis District, Mandailing Natal Regency. Households in rural areas face high economic vulnerability due to unstable income, large family dependents, as well as health and occupational accident risks, while insurance ownership rates remain low. Islamic insurance serves as an alternative financial protection based on the principle of mutual assistance (ta'awun) and is free from usury (riba), uncertainty (gharar), and gambling (maisir). This study employs a quantitative approach with a cross-sectional design. A sample of 96 households was taken using simple random sampling from a population of 1,500 households. Data were collected through a structured questionnaire using a 1-5 Likert scale, which had been tested for validity and reliability (Cronbach's Alpha 0.762). Data analysis included descriptive statistics, classical assumption tests (normality, multicollinearity, heteroscedasticity), and multiple linear regression analysis with t-test and F-test. This study concludes that economic protection needs, understanding of Islamic insurance, and community interest have a positive effect on the development of Islamic insurance. It is recommended that Islamic insurance institutions enhance education and socialization, local governments support sharia financial literacy programs, and insurance products be tailored to the economic conditions of rural communities. Keywords: Sharia Insurance Development, Economic Protection Needs, Financial Understanding, Interest